KARAKTERISASI KIMIA, FISIKOKIMIA DAN ORGANOLEPTIK JAM DAN JELLY JONJOT LABU KUNING (Cucurbita maxima) [Chemical, Physicochemical and Sensory Characterization of Jam and Jelly Made from Pumpkin Strands (Cucurbita maxima)] - Umar Santoso; Nur Djamilah; Murdijati Gardjito (Jurnal Teknologi dan Industri Pangan, 2006)
The objective of this research was to examine the contents of pectin,???carotene and sugars of the pumpkin strands, and to evaluate the effects of sugar addition and pH on the chemical, physical, and sensory characteristics of jam and jelly made from pumpkin strands. The preparation of jam and jelly were conducted with sugar addition of 55%, 60%, and 65% and pH values of 3.0, 3.2, and 3.4. The products were analyzed for moisture, sugar,???carotene, and soluble solid, and were evaluated for firmness and sensory properties.The results showed that the moisture content of jelly was between 26.36 - 35.27% and that of the jam between 39.53 - 45.67%. Beta-carotene of jelly was between 241.79 - 404.42 RE/100g (db) and that of jam was between 235.58 - 487.51 RE/100g (db). The decreasing of pH and increasing of sugar addition tended to increase the content of reducing sugars and soluble solid of the products. Jelly could be made from pumpkin strands by addition of 55% or 60% sugar, and the firmness increased by decreasing of pH value. There were no significance differences between the treatments for color, flavor and overall preference score. The addition of 60% sugar and pH of 3.2 was the best condition for making jam and jelly from pumpkin strands. Key words: Pumpkin strands, jam, jelly.